Pattern of surgical emergencies in Rural Southwestern Nigeria - Azeez Oyemomi Ibrahim; Paul O Abiola; Shuaib Kayode Aremu; Olabode M Shabi; Tosin Anthony Agbesanwa (Journal of Emergencies, Trauma and Shock, 2022)
Introduction: Considering the magnitude of deaths prevailing in the accident and emergency department (AED) in health facilities of sub-Sahara Africa, there is a need to have information on the burden of admissions and deaths due to surgical emergencies. Few studies in Nigerian hospitals in urban and suburban areas have been documented, but none in the rural setting. The objectives of this study were to ascertain the sociodemographic profile, causes and outcomes of admissions, and the pattern and causes of deaths due to surgical emergencies. Methods: A retrospective survey using a data form and a predetermined questionnaire was used to review the patients admitted for surgical emergencies at the AED of a tertiary hospital in rural southwestern Nigeria from January 2015 to December 2019. The data were analyzed using SPSS version 22.0. The results were presented in descriptive and tabular formats. Results: Surgical emergencies constituted 43.9% of all admissions. The mean age of admissions was 42 ± 16.9 years, and majorities were in the young and middle-aged groups. There were more males (66.4%) than females (33.6%). Trauma(60.9%) of which road traffic accident (RTAs)(56.0%), was the leading mechanism of trauma. The mortality rate was 5.4% and was caused majorly by RTAs (33.0%), diabetes mellitus foot ulcers (11.0%), and malignancies (9.8%). Conclusion: In this study, surgical emergencies constituted 43.9%, and a majority of the patients were male. Trauma caused by RTA is the most cause of admission. The mortality rate was 5.4%. This finding may provide an impetus for prospective research on this outcome.